Contribution of religious moderation among multicultural counseling competence - Darmawani, Evia; Suryahadikusumah, Ahmad Rofi; Nurlela, Nurlela; Surtiyoni, Endang (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The issue of religious moderation in Islamic counseling is part of the ethical and moral values of the counselor. Religious moderation education should be able to improve multicultural competence, especially in prospective Islamic counselors. This study aims to analyze whether religious moderation contributes to the development of multicultural counseling competence. The study used ex-post facto to examine the relationship between religious moderation and the multicultural counseling competence. The research was conducted through a survey using a google form to 30 students of Islamic Guidance and Counseling at UIN Sultan Maulana Hasanuddin Banten and 30 students of guidance and counseling at the University of PGRI Palembang. The results showed that religious moderation contributes to the development of multicultural counseling competencies. Religious moderation supports the development of multicultural insight regarding differences in values and a person's perspective in religion.